Fairness criteria for allocating scarce resources - Bismark Singh (Optimization Letters, 2020)
We develop an optimization model to provide a fair allocation of multiple resources to multiple users. All resources might not be suitable to all users. We develop a notion of fairness, and then provide a general class of functions achieving it. Next, we develop more restricted notions of fairness—special cases of which exist in literature. Finally, we distinguish between scarce and abundant resources, and show that if a resource is abundant, all users seeking it achieve the maximum possible coverage.
Keywords: 510; Proportional fairness; Equity; Optimization; Welfare; Resource allocation; KKT conditions